Political Ecology of spatial planning and protected areas. Crossroads in implementing Local System of Protected Areas in the Municipality of Santa Rosa de Osos, Antioquia, Colombia - Zapata Ochoa, John Dairo (Geografares, 2024)
This article examines the interaction between land use planning and nature preservation in Colombia, focusing on Santa Rosa de Osos, Antioquia. It highlights how socio-economic dynamics influence the management of natural resources, where nature conservation clashes with and adapts to economic interests. Various actors are identified, such as the State, companies, and local communities, with divergent agendas that highlight tensions between nature preservation and capitalist expansion. The challenges faced by the Santa Rosa de Osos Local Protected Areas System are discussed, especially in areas where the clash between nature preservation and capital expansion under predatory forms is increasing. It is suggested that state land use planning often fails to reflect reality or understand territorial dynamics, questioning its effectiveness.